2015
DOI: 10.1159/000437427
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Hepatitis C Infection with Pegylated Interferon and Ribavirin in Patients Coinfected with Human Immunodeficiency Virus: A Systematic Review and Meta-Analysis

Abstract: Background/Aims: Of the 35 million human immunodeficiency virus (HIV)-positive patients worldwide, 10-40% are coinfected with chronic hepatitis C virus (HCV). Compared to HCV-monoinfected patients, those coinfected experience decreased spontaneous HCV clearance, accelerated liver fibrosis, and a decreased response to anti-HCV therapy. We conducted a meta-analysis to estimate the efficacy of treating acute HCV in HIV-positive patients with peginterferon and ribavirin combination therapy. Methods: Two authors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
(122 reference statements)
1
2
0
Order By: Relevance
“…In our PLHIV population, the majority were infected with genotype 1a, followed by genotype 4 (a/c/d). This is similar to what was reported in international literature (Zhang et al, 2015). On the other hand, the majority of the PWID in the Belgian population was also infected with genotype 1a but followed by genotype 3 (Robaeys et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In our PLHIV population, the majority were infected with genotype 1a, followed by genotype 4 (a/c/d). This is similar to what was reported in international literature (Zhang et al, 2015). On the other hand, the majority of the PWID in the Belgian population was also infected with genotype 1a but followed by genotype 3 (Robaeys et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…20 Higher sustained virological response rates for patients with HCV infection were reported in the period shortly before any DAA were available when compared with results from clinical trials investigating the use of pegylated-interferon, 2 possibly because of earlier initiation of pegylated-interferon treatment. 21 There were also several studies actively recruiting MSM with HIV and early HCV infection (DAHHS1, 22 DAHHS2, 23 and REACT [NCT02625909]). However, the only large decrease in HCV infection incidence was observed in the DAHHS2 study, 23 and a modelling study has shown that no difference in HCV incidence would be observed with immediate initiation of DAA therapy compared with initiation of DAA therapy at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The SVR24 rates of pegylated IFN (PEG-INF) with or without ribavirin (RBV) for 8 to 24 weeks in acute HCV infection range from 60% to 93%. [84][85][86][87][88][89][90] Although the antiviral response rates are fair with IFN-based therapies in patients with acute HCV infection, IFN is obsolete after the introduction of DAAs owing to the concerns about treatment-emergent adverse events (AEs) and the longer treatment duration.…”
Section: Treatment With Ifn-free Daasmentioning
confidence: 99%